Strategi Pemasaran Produk Olahan Hasil Perikanan pada UMKM Cindy Group - Setiyorini, Eviet Sri; Noorachmat, Bambang Pramudya; Syamsun, Muhammad (Institut Pertanian Bogor, 2018)
Cindy Group is a company grouped as SMEs which produces boiled fish, both traditional and hygienic. Companies to keep their survival in order to survive in a competitive market, must have a strategy to attract consumers to buy their products. One of the best strategy is to evaluate and develop appropriate marketing strategies. The objectives of this research are: (1) to identify and analyze internal and external factors influencing Cindy Group marketing strategy, (2) to formulate Cindy Group marketing strategy, and (3) to prioritize Cindy Group marketing strategy. Based on internal and external factors, Cindy Group formulated strengths, weaknesses, opportunities and threats toward marketing strategy using Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE). The total score in the IFE and EFE matrices illustrated that the firm's stable position in responding to external situations. The total IFE score of 3.3436 indicated that the strengths of Cindy Group could overcome the weaknessess very well. Total EFE score of 2.5545 indicated that Cindy Group was good enough to respond the opportunities and minimize threats. Based on QSPM analysis, the priority strategy to be applied in the marketing of fishery processed products at UMKM Cindy Group which was expanding marketing network, maintaining quality, increasing sales service and increasing cooperation with related institutions and cooperatives/other SMEs in order to get raw material access.